2015
DOI: 10.1089/jmf.2014.3353
|View full text |Cite
|
Sign up to set email alerts
|

Red Bean Extract Inhibits Lipopolysaccharide-Induced Inflammation and H2O2-Induced Oxidative Stress in RAW 264.7 Macrophages

Abstract: Red bean (Phaseolus radiatus L. var. Aurea) is a leguminous seed and mainly used as one of the popular ingredients in oriental desserts. The objective of this study was to evaluate the anti-inflammatory activity of 50 g/kg ethanolic extract of red bean (RBE) by measuring lipopolysaccharide (LPS)-induced expressions of nitric oxide (NO), inducible nitric oxide synthase (iNOS), cyclooxygenase 2 (COX-2), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) in RAW 264.7 macrophages. On the other hand, the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Red beans are small, soft red textured, oval-shaped beans. They exert an anti-inflammatory response [ 20 ] and have health-promoting potential with anti-fungal, immunomodulatory, anti-proliferative and apoptosis-inducing activities in tumor cells [ 21 , 22 ]. Black beans are known as turtle beans, which are sweet in taste, soft texture, medium-sized, and oval-shaped beans.…”
Section: Common Beans and Their Health Benefitsmentioning
confidence: 99%
“…Red beans are small, soft red textured, oval-shaped beans. They exert an anti-inflammatory response [ 20 ] and have health-promoting potential with anti-fungal, immunomodulatory, anti-proliferative and apoptosis-inducing activities in tumor cells [ 21 , 22 ]. Black beans are known as turtle beans, which are sweet in taste, soft texture, medium-sized, and oval-shaped beans.…”
Section: Common Beans and Their Health Benefitsmentioning
confidence: 99%
“…SOD catalyzes superoxide anions into H 2 O 2 and O 2 , to achieve the purpose of scavenging free radicals. It plays a crucial role in the balance of oxygen utilization by the body ( 38 ). Both CAT and GSH-Px are important peroxidase enzymes that exist widely in the body.…”
Section: Resultsmentioning
confidence: 99%
“…Yen et al (2006) revealed the free radical-scavenging and protective effects of lotus seed extracts against reactive nitrogen, sodium nitroprusside, peroxynitrite-induced cytotoxicity, and DNA damage in the macrophage RAW 264.7 cell line. Chao et al (2015) also reported that the ethanolic extract of red bean (RBE) can diminish H2O2-induced oxidative damage in RAW 264.7 macrophages. Phenolic compounds and cyanidin-3-O-glucoside from the RBE may have efficacy as overall in vitro anti-inflammatory and antioxidant agents.…”
Section: Discussionmentioning
confidence: 97%